ANALISIS RASIO ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN KEPAHIANG TAHUN 2013-2017 - Yun Fitriano; Ahmad Soleh; Revaldo Khairullah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2020)
The purpose of this study is to find out: 1) the financial performance of Kepahiang Regency Government based on the results of the calculation of the independence ratio, 2) the financial performance of the Kepahiang Regency Government based on the results of the calculation of fiscal decentralization degree ratios, 3) the financial performance of Kepahiang Regency Government based on the results of calculation of the effectiveness ratio, 4) the financial performance of the Kepahiang Regency Government based on the results of the calculation of financial efficiency ratios, 5) the financial performance of the Kepahiang Regency Government based on the results of the calculation of the financial dependency ratio. The data were collected using documentation and analyzed through financial ratios. The results of the study revealed the regional financial likelihood ratio with an average ratio of 4.70% in the interval 0% -25% with very low criteria and intrurctive relations patterns, meaning that the Regional Government of Kepahiang Regency was not yet independent. Fiscal decentralization degree ratio with an average ratio of 4.45% at an interval of 0.00% -10% with very poor criteria, meaning that the Regional Government of Kepahiang Regency has not been able to carry out decentralization or the authority and responsibility given by the Central Government to the Government Area. The effectiveness ratio with an average ratio of 103.82% with very effective criteria, means that the Regional Government of Kepahiang Regency is able to realize the budget or PAD targets that have been set even though in 2014 and 2017 were quite effective and 2015 was less effective. Regional financial efficiency ratio with an average ratio of 90,84% with the criteria of less efficient, meaning that regional spending or expenditure in Kepahiang Regency is still very high compared to PAD. Regional financial dependency ratio with an average ratio of 94,63% with very high criteria, meaning that the Regional Government of Kepahiang Regency has a very high dependence on the Provincial Government and the Central Government to finance regional expenditure.Â Keywords: Ratio, Regional Income and Expenditure Budget